Free resolutions of Dynkin format and the licci property of grade $3$ perfect ideals - Christensen, Lars Winther; Veliche, Oana; Weyman, Jerzy (MATHEMATICA SCANDINAVICA, 2019)
Recent work on generic free resolutions of length $3$ attaches to every resolution a graph and suggests that resolutions whose associated graph is a Dynkin diagram are distinguished. We conjecture that in a regular local ring, every grade $3$ perfect ideal whose minimal free resolution is distinguished in this way is in the linkage class of a complete intersection.